Molecular mechanisms of hair growth and regeneration: current understanding and novel paradigms - Houschyar, Khosrow Siamak; Borrelli, Mimi R.; Tapking, Christian; Popp, Daniel; Puladi, Behrus; Ooms, Mark; Chelliah, Malcolm P.; Rein, Susanne; Pförringer, Dominik; Thor, Dominik; Reumuth, Georg; Wallner, Christoph; et al. (Dermatology, 2020)
Hair is a defining feature of mammals and has critical functions, including protection, production of sebum, apocrine sweat and pheromones, social and sexual interactions, thermoregulation, and provision of stem cells for skin homeostasis, regeneration, and repair. The hair follicle (HF) is considered a “mini-organ,” consisting of intricate and well-organized structures which originate from HF stem and progenitor cells. Dermal papilla cells are the main components of the mesenchymal compartments in the hair bulb and are instrumental in generating signals to regulate the behavior of neighboring epithelial cells during the hair cycle. Mesenchymal-epithelial interactions within the dermal papilla niche drive HF embryonic development as well as the postnatal hair growth and regeneration cycle. This review summarizes the current understanding of HF development, repair, and regeneration, with special focus on cell signaling pathways governing these processes. In particular, we discuss emerging paradigms of molecular signaling governing the dermal papilla-epithelial cellular interactions during hair growth and maintenance and the recent progress made towards tissue engineering of human hair follicles.
Gesehen am 17.09.2020